Математическое моделирование тепловых процессов при поверхностном упрочнении элементов конструкций - Веселовский, В. Б.; Малая, Ю. А.; Губин, А. И.; Ляшенко, В. И. (НТУ "ХПИ", 2011)
The mathematical model of thermal processes at surface strengthening of multilayer constructions elements has been developed on the basis of the generalized heat conduction law. The proposed model takes into account the finite speed of heat propagation and nonideal thermal contact at the junctions of layers. The boundary problem is solved byan operational method. The study of the obtained solution and calculations of temperature fields have been performed.
Keywords: температурное поле; оптические свойства; поглощенная энергия; импульсный нагрев